Aid Suspensions as Coercive Tools? The European Union’s Experience in the African-Caribbean-Pacific (ACP) Context - PORTELA, Clara (Institutional Knowledge at Singapore Management University, 2007)
Since the signing of the Cotonou Agreement in 2000, the European Union (EU) has suspended development aid towards a number of African Caribbean and Pacific (ACP) countries in response to breaches of Human Rights and democratic principles by activating the so-called Human Rights clause (article 96). The present article analyses the use by the EU of aid suspensions as political tools and their efficacy in achieving the desired policy goals, in an attempt to identify and explain the determinants leading to the success of these measures. The investigation finds that the use of development aid suspensions is frequently effective. Classical sanctions theory appears to account largely for their success, given that most targets display a significant degree of dependence on the EU as a donor or a trading partner. However, and without refuting the explanatory power of that approach, a closer look at this practice unveils a number of factors that contribute to facilitate success. One of them is the selective use of the tool: suspensions are applied predominantly in cases of interruptions of the democratic process, while they are rarely used in situations of violent conflict. The specificities of the consultations mechanism, and especially the attitude of ACP neighbouring countries- often openly supportive-, largely determine the final outcome.